Podoba Dunaja v slovenski književnosti - Smolej, Tone (Slavistična revija, 2008)
Austrian literary criticism has treated the image of Vienna in Slovene literature. Maria Vera Claricini (1996) contributed a study about Cankar's Vienna for an extensive collection of papers, Wien als Magnet. A more innovative study is by Stefan Simonek (2004), who analyzed primarily the world of Viennese parks in Cankar's literature. The main Slovene literary scholar who treated this topis is without a doubt our honoree, France Bernik (1998). While the previous scholars mostly focused on Cankar, the present study attempts to present other Slovene portrayers of Vienna and thus outline some constant features in Slovene image of this city.
Keywords: Dunaj; history of literature; literarna zgodovina; literarne študije; Slovene literature; slovenska književnost; Vienna